2011
DOI: 10.1017/s1368980010003356
|View full text |Cite
|
Sign up to set email alerts
|

Shared environments: a multilevel analysis of community context and child nutritional status in Bangladesh

Abstract: Objective: The goal of the present study was to examine the influence of community environment on the nutritional status (weight-for-age and height-forage) of children (aged 0-59 months) in Bangladesh. In addition, we tested the association between specific characteristics of community environments and child nutritional status. Design: Cross-sectional survey. Setting: The data are from the nationally representative 2004 Bangladesh Demographic and Health Survey. Subjects: Respondents were ever-married women (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 48 publications
4
15
0
1
Order By: Relevance
“…Our results confirm the importance of the education of mothers for the health of children, found in previous studies for Colombia 10 , 11 and developing countries 23 , 24 . Education level may influence the health of the children from the access to information or the ability to acquire new knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirm the importance of the education of mothers for the health of children, found in previous studies for Colombia 10 , 11 and developing countries 23 , 24 . Education level may influence the health of the children from the access to information or the ability to acquire new knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…through contact with contaminated flies or other children) spread faecal contamination and water contamination over the community. In this way, members of households that already have good water and sanitation may be affected (Corsi et al, 2011;Gragnolati, 1999). Hence, important spillover effects between factors at the household and at the community level can be relevant.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This might facilitate better hygiene and health outcomes for children in the community (Corsi et al, 2011;Gragnolati, 1999). An even stronger spillover effect is expected with respect to the coverage of proper sanitation in the community (Alderman et al, 2003).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Communities often share common characteristics such as customs, beliefs and values, and may also have common access to resources such as income, transport, markets, schools and health centres. Previous studies have found associations between child nutritional status and the education level of the community (Corsi et al, 2011); economic inequality at the provincial level (Larrea and Kawachi, 2005) and access to clean water and environmental conditions (Pongou et al, 2006).…”
Section: Introductionmentioning
confidence: 99%